FABRICATION AND CHARACTERIZATION STUDIES OF LITHIUM-BORATE RUBY GLASSES CONTAINING GOLD NANOPARTICLES - Shivaprakash, Y.; Anavekar, R.V. (International Journal of Research -GRANTHAALAYAH, 2017)
Glasses containing Au nanoparticles have been synthesized in the base glass of composition 30Li2O–70B2O3 using gold chloride (HAuCl4.3H2O) as a dopant. The characteristic ruby color has been observed which is attributed due to surface plasmon resonance of the Au nanoparticles. The hue of the color increases with the increase of concentration of the dopant. Presence of the gold nanoparticles has been confirmed by studying the optical absorption spectra in the visible range which show a characteristic absorption peak at 560nm. XRD and SEM studies show that the addition of Au increases the kinetics of growth and crystallization. ESR studies indicate that the electronic state of gold is either Au0 or Au+.